Echocardiographic Imaging of Intracardiac Thrombus and Evaluated its Underlying cause along Therapeutic Implications: A Review - Haque, Mostashirul; Kabir, Mohammad Faisal Ibn; Amin, Md Rasul; Khaled, Md Fakhrul Islam; Mandal, Rayhan Masum; Zaman, S M Mustafa; Hoque, Harisul; Rahman, Fazlur; Ahmed, Choudhury Meshkat (University Heart Journal, 2020)
Abstract not available University Heart Journal Vol. 16, No. 1, Jan 2020; 40-42